Plasmodium falciparum resistance to artemisinin-based combination therapies. (October 2022) - Ward, Kurt E; Fidock, David A; Bridgford, Jessica L
Abstract : Multidrug-resistant Plasmodium falciparum parasites are a major threat to public health in intertropical regions. Understanding the mechanistic basis, origins, and spread of resistance can inform strategies to mitigate its impact and reduce the global burden of malaria. The recent emergence in Africa of partial resistance to artemisinins, the core component of first-line combination therapies, is particularly concerning. Here, we review recent advances in elucidating the mechanistic basis of artemisinin resistance, driven primarily by point mutations in P. falciparum Kelch13, a key regulator of hemoglobin endocytosis and parasite response to artemisinin-induced stress. We also review resistance to partner drugs, including piperaquine and mefloquine, highlighting a key role for plasmepsins 2/3 and the drug and solute transporters P. falciparum chloroquine-resistance transporter and P. falciparum multidrug-resistance protein-1. Highlights: Mutant K13-mediated artemisinin resistance involves reduced hemoglobin endocytosis. Artemisinin partial resistance has emerged in Africa. Novel PfCRT mutations drive high-grade piperaquine resistance in Southeast Asia. PfCRT and PfMDR1 mutations impact solute and drug transport in P. falciparum .